Consumer attitudes and misperceptions associated with trends in self-reported cereal foods consumption: Cross-sectional study of Western Australian adults, 1995 to 2012 - Pollard, Christina; Pulker, Claire; Meng, X.; Scott, Jane; Denham, F.; Solah, Vicky; Kerr, Deborah (BioMed Central Ltd, 2017)
Background: The reasons for low adherence to cereal dietary guidelines are not well understood but may be related to knowledge, attitudes, beliefs and perceived barriers. This study aims to assess trends in cereal foods consumption, intention to change and factors associated with intake among Western Australian (WA) adults 18 to 64 years. Method: Cross-sectional data from the 1995, 1998, 2001, 2004, 2009, and 2012 Nutrition Monitoring Survey Series involving 7044 adults were pooled. Outcome variables: types and amount of cereals (bread, rice, pasta, and breakfast cereal) eaten the day prior. Attitudes, knowledge, intentions, weight status and sociodemographic characteristics were measured. Descriptive statistics, multiple binary logistic and multinomial logistic regressions assess factors associated with consumption. Results: Bread (78%) was the most commonly consumed cereal food. The proportion eating bread decreased across survey years (Odds Ratio OR = 0.31; 95% Confidence Interval; 0.24-0.40 in 2012 versus 1995), as did the amount (4.1 slices of bread in 1995 to 2.4 in 2012). The odds of consuming whole-grain cereal foods increased since 2009 (OR = 1.27; 1.02-1.58 versus 1995 p < 0.05). The likelihood of trying to eat less cereal food in the past year was greater in 2012 compared to 1995 (Relative Risk Ratio RRR 10.88; 6.81-17.4). Knowledge of cereal recommendations decreased over time (OR = 0.20; 0.15-0.27 in 2012 versus 1995 p < 0.001). Overweight and obese respondents were more likely than healthy weight respondents to have tried to eat less cereals (RRR 1.65; 1.22-2.24 and 1.88; 1.35-2.63 respectively). 'I already eat enough' was the main barrier (75% in 1995 to 84% in 2012 (p < 0.001)). Conclusions: WA adults are actively reducing the amount of cereal foods they eat and intake is associated with a misperception of adequacy of intake. Nutrition intervention is needed to increase awareness of the health benefits of cereal foods, particularly whole-grains, and to address barriers to incorporating them daily. © 2017 The Author(s).